A Case of a Spinal Extradural Arachnoid Cyst - Yousuke Kojimahara; Shintaro Tsuge; Keiji Hasegawa; Katsunori Fukutake; Kazumasa Nakamura; Akihito Wada; Hiroshi Takahashi (Case Reports in Orthopedics)
The patient was a 49-year-old woman with a chief complaint of hip and buttock pain that had persisted for 3 years. She visited our hospital for aggravation of the pain. Percussion tenderness of the spinous process was observed and a T1-low, T2-high cystic lesion was detected on the dorsal side of the dural canal at the 12th thoracic vertebral level on MRI performed by a previous physician. Plane CT showed severe scalloping at the same level. During laminectomy for the 11th and 12th thoracic vertebrae, a cystic lesion of about 60×25 mm was noted on the dorsal side of the dural canal, with a communication pathway with the cyst present near the left 12th nerve root bifurcation. This pathway was ligated and the cyst was excised. The histopathological diagnosis was an arachnoid cyst. Pain improved after surgery, and as of 10 months after surgery, the cystic lesion has not recurred. A spinal extradural arachnoid cyst (SEAC) is a relatively rare disease. This case shows that surgical ligation of a communicating tract and cystectomy are necessary and contrast-enhanced CT was useful for the identification of the position of the communication pathway before surgery.